PENGARUH FAKTOR TEKNOLOGI DAN STRATEGI INOVASI TERHADAP NILAI EKSPOR PERUSAHAAN MANUFAKTUR DI INDONESIA - Widiastuti, Imron (SISTEM Jurnal Ilmu Ilmu Teknik, 2013)
The study extent to the D’Angelo (2012), Flor, Rodríguez and Rodríguez (2011), and also Nassimbeni (2001)  escpecially looking for empirically agreement for effect ofinternal factors technology and innovation capacity) on export performance found the insignificant relationship between technology levers and export performance at small-sized enterprises. The previous findings on the export performance model were cross culture, thus the empirical investigation in Indonesian context will more validated the issue. The study aims to test the effect of technology and innovation capacity on the large and medium-sized manufacturer’s export performance. Based on given population as sample frame, the sample was drawn by stratified random sampling. The analysis is conducted to 61 research’s participants, which is collected by mail-survey to the company director. The company director was believed having the valid perception about each items questionnaire’s answer. Based on the linier model, the study shown that a technology lever has the regression coefficient 0,268 and effect statistically significant on the export performance at p-value 2,3%.. Furthermore, the innovation capacity has the regression coefficient 0,292 at p-value 1,3%. The direction of the variable is consistent to Nassimbeni’s study.  The other important findings are age and employee number of the company wasn’t seemed as determinant of export success, but the capability of manage-ment to accommodate the export market characteristic in the major one. The study also finds the positif asset effect on export performance. It supported the previous study in resource-based paradigm.